The synthesis and mechanical properties of high pure Ti2Al(Sn)C solid solution. Issue 5 (13th April 2018) - Cai, Leping; Huang, Zhenying; Hu, Wenqiang; Lei, Cong; Wo, Shaoshuai; Li, Xinkang; Zhai, Hongxiang; Zhou, Yang
Abstract: High pure Ti2 Al(1− x ) Sn x C ( x = 0‐1) powders were synthesized using Ti, Al, Sn, and TiC powders as raw materials by pressureless sintering method. The influence of sintering temperature and raw material ratio on the purity of Ti2 AlC and Ti2 Al0.8 Sn0.2 C powders were investigated. The results show that pure Ti2 AlC and Ti2 Al0.8 Sn0.2 C powders were obtained from the mixed raw materials ratio of Ti:1.1Al:0.9TiC and Ti:0.9Al:0.2Sn:0.9TiC at 1450°C, respectively. Subsequently, fully dense Ti2 AlC and Ti2 Al0.8 Sn0.2 C bulks were prepared using mechanically alloying and hot pressed sintering method. The Vickers hardness of Ti2 AlC and Ti2 Al0.8 Sn0.2 C approaches approximately about 6 GPa and 4 GPa, the flexural strength was measured to be 650 ± 36 MPa and 521 ± 33 MPa, respectively. Microstructural analysis reveals that grain delamination, kink bands, and crack deflection occurred around the indentation area and at the fracture surface.